Bentuk Gangguan Disosiatif Tokoh Utama dalam Novel Tell Me Your Dreams Karya Sidney Sheldon (Forms of Dissociative Disorder Main Character in Tell Me Your Dreams Novel by Sidney Sheldon) - Septy Riyani; Yumna Rasyid; Asti Purbarini (Indonesian Language Education and Literature, 2022)
Sidney Sheldon's novel Tell Me Your Dreams is one of the novels with the theme of dissociative disorder, namely a personality disorder in which an individual has more than one distinct personality. The purpose of this research is to describe the main character's personality, the forms of dissociative disorder experienced by the main character, as well as the causes and effects of dissociative disorder in the main character. The method used in this study is a descriptive qualitative method using a literary psychology approach. The results of the analysis show that the character Ashley Patterson has several dissociative disorders. Ashley's forms of dissociative disorder include dissociative amnesia, dissociative fugu, dissociative identity, and depersonalization. Dissociative disorders are divided into three parts which can be seen from their characteristics, form, and causes, namely having multiple personalities.Novel Tell Me Your Dreams karya Sidney Sheldon adalah salah satu novel yang mengangkat tema gangguan disosiatif, yakni gangguan kepribadian di mana seorang individu memiliki lebih dari satu kepribadian yang berbeda. Tujuan penelitian ini adalah untuk mendeskripsikan kepribadian tokoh utama, entuk gangguan disosiatif yang dialami tokoh utama, serta penyebab dan akibat gangguan disosiatif pada tokoh utama. Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskriptif dengan menggunakan pendekatan psikologi sastra. Hasil analisis menunjukkan bahwa tokoh Ashley Patterson memiliki beberapa gangguan disosiatif. Bentuk gangguan disosiatif yang dialami Ashley, meliputi: amnesia disosiatif, fugu disosiatif, identitas disosiatif dan depersonalisasi. Gangguan disosiatif dibagi tiga bagian yang dapat dilihat dari ciri-ciri, bentuk, dan penyebabnya, yakni berkepribadian majemuk.